Emotional Intelligence and Well-Being of Special Education Teachers in China: The Mediating Role of Work-Engagement - Fu, Wangqian; Wang, Chonggao; Tang, Wenjun; Lu, Sha; Wang, Yan (Frontiers in Psychology, 2021)
The well-being of special education teachers is key to their mental health and also influences the development of their students. This study aimed to investigate the psychological mechanism of the well-being of special education teachers in China, where they are maximum in number. We explored the role of emotional intelligence (EI) and work engagement on the well-being of teachers. A total of 496 Chinese special education teachers participated in the current study. Results suggested that (1) the EI and work engagement were positively associated with the well-being of special education teachers; and that (2) work engagement played a mediating role on EI and well-being of special education teachers. To promote the well-being of special education teachers, suggestions for policymakers and schools are discussed.